Super Refractory Status Epilepticus in a Case of Post Mumps Autoimmune Encephalitis: A Rare Case Report - Giri, Satabdi; Agrawal, Priyanka; Kumari, Mamta; Dash, Dillip Kumar (Journal of Nepal Paediatric Society, 2019)
Seizure is a common problem in many paediatric patients. When seizures persist even after 24 hrs of anaesthetic treatment it is known as Super Refractory Status Epilepticus (SRSE). We report a 10 years old girl admitted with fever, altered sensorium and GTCS with a provisional diagnosis of viral encephalitis. In the line of SRSE infusion thiopental was also started after giving first line antiepileptic as per guidelines. Seizures persisted despite six anti-epileptic drugs, steroids and infusion anaesthetic. MRI brain was suggestive of T2W Flair hyperintensity in B/L hippocampal and Para-hippocampal gyrus and CSF and blood positive for Mumps IgM. This was suggestive of Mesial temporal sclerosis (MTS) which is the scarring and loss of neurons in the deepest portion of the temporal lobe due to oxygen starvation to the brain, head trauma, brain infection or without any apparent cause. Dramatic response was seen after 36-48 hours of IVIG administration.